Ujaran Kebencian dalam Kolom Komentar YouTube pada Tahun Politik Pemilihan Presiden 2019 - Fitri Jamilah; Primasari Wahyuni (Silampari Bisa: Jurnal Penelitian Pendidikan Bahasa Indonesia, Daerah, dan Asing, 2020)
YouTube as social media is not only a means of communication in social interactions, but can also be used as a means of political communication. As a means of political communication, YouTube is often used to convey opinions and support for political figures who are promoted through communication, especially seen in the comments column. Various communication styles are carried out by social media users, either through comments, criticisms, suggestions, and jokes, which have the opportunity to contain hate speech. This article is the result of qualitative research that focuses on interpreting the data that has been obtained with an in-depth explanation of the phenomenon of using hate speech in the comments column of the Youtube Channel for political news in Indonesia. Data that has been successfully extracted, collected, and recorded in research activities. The technique of testing the validity of the research data used member check and validation of media experts. The results of this study indicate that the hate speech that occurred in the 2019 presidential election political news on the YouTube channel is in the form of words and phrases, as well as the use of language styles. The language style of hate speech in this study is dominated by sarcasm, which means rude, contains cursing, insinuation, ridicule, and the use of names or nicknames for others with disrespect or even humiliation or insult.